"The glory of each generation is to set its own precedent": Belva Lockwood and the rhetorical construction of female presidential plausibility. (2nd January 2019) - Paup, Emily Berg
Abstract: This study seeks to understand the rhetorical tactics of Belva Bennett Lockwood, the first woman to run a campaign for U.S. President. Lockwood attempted to make a female presidential candidacy seem plausible by framing her actions as culturally expected, befitting for a woman, and prototypical for future female politicians. Through her use of rhetorical eikos, she seemed to suggest that female political leadership was not just probable but needed in the political culture of the time. A close reading of her campaign speeches and writings reveals the potential of eikotic logos to present a female presidential candidacy as innate, and thus logical, legitimate, and part of an essential future. This essay will present a historical review of Lockwood's unprecedented political campaigns, an analysis of the theoretical potential of eikos argument as seen through her rhetoric, and commentary on the state of women and cultural perceptions of presidentiality then and now.